A rare case presentation: pregnancy and gastric carcinoma - Yildiz, Mustafa (BMC Gastroenterol, 2020)
BACKGROUND: Gastrointestinal system (GIS) malignancy with pregnancy is a very rare condition and is not common outside Japan. The incidence is between 0.025–0.1% for each pregnancy. GIS malignancies are diagnosed late in pregnancy and detected at an advanced stage. The most common cause of this condition is that the symptoms such as vomiting, nausea, loss of appetite and abdominal growth are mistaken with pregnancy and malignancy is overlooked. Especially in the second trimester, symptoms such as nausea and vomiting, weight loss, melena, hematemesis and deep anemia should suggest malignancy. Upper GIS endoscopy and colonoscopy are the recommended screening methods in these patients, especially in the third trimester. CASE PRESENTATION: We present a rare case presenting to our emergency room with the complaint of bloody vomiting, at the 36th week of gestation with a live singleton pregnancy, and receiving the diagnosis of undifferentiated gastric carcinoma from the biopsy taken from the ulcerated lesion on the stomach cardia, with upper GIS endoscopy performed due to deep anemia, who underwent simultaneous cesarean section and subtotal gastrectomy. CONCLUSION: Gastrointestinal system (GIS) malignancy with pregnancy is a very rare condition, but it should be considered when symptoms such as nausea and vomiting, weight loss, melena, hematemesis and deep anemia occur, especially in the second trimester, and endoscopic screening should be recommended. Because of the delay in diagnosis of malignancy and the detection in advanced stages, patients should be referred for treatment without delay.